Light curing infection control barriers: do some types jeopardize the concept of conventional bulk-fill composites? - Dalia I. Sherief; Mohamed M. Kandil; Dina Ahmed El-Refai (BMC, 2024)
Abstract Background Using infection control barriers (ICBs) on light curing units (LCUs) became mandatory to achieve proper infection control measures without jeopardizing the integrity of the restorations, especially at deeper layers. This study explored the effect of two ICBs on the irradiance of the LCU, as well as the degree of conversion (DC) and flexural strength (FS) of two types of bulk-fill composites. Water vapor permeability (WVP) of both barriers was also assessed to evaluate the capability of such barriers to prevent transmission of blood and saliva droplets and aerosols. Methods Two bulk-fill composites (X-tra fil and Tetric N- ceram) and two ICBs (Pinnacle Cure sleeve and Sanita wrapping film) were used in this study. Light irradiance was recorded per experimental condition using spectroradiometer. For DC and FS, specimens of 4 mm thickness were prepared. Each specimen was composed of two separable upper and lower layers of thickness 2 mm. DC and FS were measured using Infra-red spectroscopy and three-point loading test respectively. WVP was investigated using the cup method. Means and standard deviations were calculated, and the data were statistically analyzed using factorial analysis of variance test (α = 0.05). Results Light irradiance showed highest values using no ICBs and lowest values using Pinnacle curing sleeve. Both bulk-fill composites showed higher DC mean values without ICBs and when using Sanita wrapping film for both upper and lower layers of the specimens compared to Pinnacle curing sleeve. The upper layers of composite specimens showed higher DC compared to lower layers for all experimental conditions. Both ICBs had no adverse effect on FS of both composites' upper layers. Pinnacle sleeve significantly reduced FS of both composites' lower layers. X-tra fil showed higher DC and FS compared to Tetric N-Ceram for all experimental conditions. Regarding WVP; the wrapping film showed higher WVP compared to the curing sleeve. Conclusions Sanita wrapping film can be used as a successful ICB, without jeopardizing the concept of bulk-fill composites. Pinnacle cure sleeve can be considered an effective ICB, however its influence on properties and serviceability of bulk-fill composites remains questionable.